ANALISIS DAMPAK PRAKTIK IHTIKAR DALAM PERDAGANGAN MASKER DI MASA PANDEMI COVID-19 (STUDI KASUS TOKO LAILAQUEEN BANGKINGAN KOTA SURABAYA) - Nurandari, Ratrie; Anwar, Mochammad Khoirul (Jurnal Ekonomika dan Bisnis Islam, 2021)
Islam commands its people to work hard so as not to be lazy. In working there are rules that must be observed so as not to merely seek and gain profit in any way. One of the jobs used by several actors is mask actors who practice ihtikar. The practice of ihtikar or more often referred to as hoarding of goods is an activity of buying goods in large quantities with the aim of being stockpiled and resold when the price of the goods has soared. The purpose of this study is to determine the buying and selling behavior of ihtikar masks in an Islamic economic perspective. This type of research is field observation. Data collection methods using interviews and observation. The nature of this research is descriptive qualitative, that is, it describes the problems obtained through the facts on the hoarding of masks that occurred in the Lailaqueen Store which is seen from the point of view of Islamic economics. The results of this study are the practice of ihtikar carried out by the Lailaqueen Store starting from the covid-19 pandemic, and the type of goods stockpiled is One Care 3ply masks with medical quality. The purpose of this ihtikar practice is to gain multiple benefits, resulting in misery for others because masks are becoming scarce in the market.